Framing Student Perspectives into the Higher Education Institutional Review Policy Process - Poth, Cheryl (Canadian Journal of Higher Education, 2015)
It is necessary and desirable to enhance student learning in higher education by integrating multiple perspectives during institutional policy reviews, yet few examples of such a process exist. This article describes an institutional assessment policy review process that used a questionnaire to elicit 269 students’ perspectives on a draft policy document. Among the key findings were a lack of focus on using assessment to inform instruction, and a lack of clarity around the purposes for assessment. Within the final policy, there seemed to be an absence of focus on assessment as supporting learning and informing instruction, although there was a significant focus on the role of assessment in measuring achievement, despite students’ emphasis on the former two characteristics. The study’s implications point to the important theoretical contributions students offer to institutional policy reviews, and the practical challenges institutions face in providing mechanisms that facilitate engagement and reflect shifts in culture.